2013
DOI: 10.1093/ije/dyt172
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure and offspring cognition and school performance. A ‘Mendelian randomization’ natural experiment

Abstract: Background There is substantial debate as to whether moderate alcohol use during pregnancy could have subtle but important effects on offspring, by impairing later cognitive function and thus school performance. The authors aimed to investigate the unconfounded effect of moderately increased prenatal alcohol exposure on cognitive/educational performance.Methods We used mother-offspring pairs participating in the Avon Longitudinal Study of Parents and Children (ALSPAC) and performed both conventional observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 51 publications
5
71
1
Order By: Relevance
“…Mendelian randomization studies using the Avon Longitudinal Study of Parents and Children predicted different patterns of PAE and variable outcomes in offspring depending on several variants in the alcohol dehydrogenase gene in the mother or child (eg, ADH1B [OMIM 103720], predictive of reduced alcohol consumption and associated with higher academic achievement in offspring). 29,30 Furthermore, regarding the direct role of genes involved in alcohol metabolism in modifying risk, evidence from laboratory studies using ethanolsensitive and ethanol-resistant chickens, mice, and zebra fish provides insight into the multifactorial genetics of ethanol-mediated cell signaling disruption and neural crest apoptosis. 31 We observed that children of mothers who reported feeling the effects of alcohol quickly or very quickly exhibited larger craniofacial differences in most exposure groups.…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian randomization studies using the Avon Longitudinal Study of Parents and Children predicted different patterns of PAE and variable outcomes in offspring depending on several variants in the alcohol dehydrogenase gene in the mother or child (eg, ADH1B [OMIM 103720], predictive of reduced alcohol consumption and associated with higher academic achievement in offspring). 29,30 Furthermore, regarding the direct role of genes involved in alcohol metabolism in modifying risk, evidence from laboratory studies using ethanolsensitive and ethanol-resistant chickens, mice, and zebra fish provides insight into the multifactorial genetics of ethanol-mediated cell signaling disruption and neural crest apoptosis. 31 We observed that children of mothers who reported feeling the effects of alcohol quickly or very quickly exhibited larger craniofacial differences in most exposure groups.…”
Section: Discussionmentioning
confidence: 99%
“…An observational analysis of children's IQ at age 8 and educational achievement at age 11 showed modest improvements in the children born to mothers who had consumed a moderate amount of alcohol during early pregnancy compared with mothers who had abstained, yet the quasi-experimental method using Mendelian randomisation on the same cohort showed that even small levels of alcohol consumption were associated with reduced educational attainment 33. The authors argue that the positive association seen in the observational study reflected residual confounding with factors associated with maternal social position and education.…”
Section: Alcohol Use In Pregnancy and Its Associated Harmsmentioning
confidence: 99%
“…Studies of maternal alcohol consumption in OECD countries suggest that women from upper socioeconomic groups are more likely to drink alcohol during pregnancy [24][25][26][27][28][29][30][31][32] but have significantly lower rates of FASD than women in lower socioeconomic groups [23]. One recent study has found that women from more socially disadvantaged backgrounds are more likely to either abstain or binge drink during pregnancy, while those who are from more socially advantaged backgrounds are more likely to drink consistently at low to moderate levels [33]. The relationship between socioeconomic status, ethnicity and alcohol consumption during pregnancy adds further complexity.…”
Section: Epidemiological Puzzles In Relationships Between Maternal Almentioning
confidence: 99%